Mapping the Future of Halal Tourism Research: Bibliometric Analysis Using VOSviewer - Marwah Qodarsyah Ramadhan Ramadhan; Kamilatus Salsabila; Rahmayati Koto (ASEAN Journal of Halal Study, 2026)
Halal tourism has emerged as one of the fastest-growing segments of the global tourism industry, driven by expanding Muslim populations and increasing demand for Shariah-compliant travel services. Despite significant scholarly attention, the field lacks a systematic mapping of its intellectual landscape across major academic databases. This study employs a bibliometric analysis of 189 documents from Scopus and 956 documents from Google Scholar, retrieved using the keyword "halal tourism". Keyword co-occurrence analysis was performed using VOSviewer with title and abstract fields, binary counting, a minimum occurrence threshold of 10, and 85 terms meeting the threshold. Publication output grew substantially from 2016, peaking between 2020 and 2024. Four major research clusters were identified: (1) tourist behavioral intention and psychology, (2) halal destination and food attributes, (3) halal tourism policy and industry opportunities, and (4) regional and religious tourism studies. The Journal of Islamic Marketing and Tourism Management Perspectives dominated the outlet landscape, with Mohamed Battour as the most prolific authorHalal tourism research is maturing, with an evolving focus from conceptual frameworks toward behavioral and experience-based inquiries. Future research should address non-Muslim tourist perspectives, post-pandemic recovery, and digital halal tourism ecosystems.